Three Sisters [large type] - Mallery, Susan (Mallery, Susan. Blackberry Island novel., 2013)
After being jilted at the altar, Andi Gordon makes the most impetuous decision of her life - buying one of the famed Three Sisters Queen Anne houses on Blackberry Island. Now the proud-ish owner of the trio's ugly duckling, she plans to open her own pediatric office on the first floor, just as soon as her hunky contractor completes the work. Andi's new future may be coming together, but the truth is she's just as badly in need of a major renovation as her house.